Advances in pediatrics in 2017: current practices and challenges in allergy, endocrinology, gastroenterology, genetics, immunology, infectious diseases, neonatology, nephrology, neurology, pulmonology from the perspective of Italian Journal of Pediatrics - Carlo Caffarelli; Francesca Santamaria; Dora Di Mauro; Carla Mastrorilli; Silvia Montella; Bertrand Tchana; Giuliana Valerio; Alberto Verrotti; Mariella Valenzise; Sergio Bernasconi; Giovanni Corsello (BMC, 2018)
Abstract This review provides an overview of a remarkable number of significant studies in pediatrics that have been published over the past year in the Italian Journal of Pediatrics. We have selected information from papers presented in the Journal that deal with allergy, endocrinology, gastroenterology, genetics, immunology, infectious diseases, neonatology, nephrology, neurology, pulmonology. The relevant epidemiologic findings, and developments in prevention, diagnosis and treatment of the last year have been discussed and placed in context. We think that advances achieved in 2017 will help readers to make the future of patients better.